Enhancement of laryngeal contrasts in non-native English clear speech: a comparison between L2-immersed sequential bilinguals and L1-immersed speakers - Jung, Ye Jee; Dmitrieva, Olga (Frontiers in Human Neuroscience, 2024)
Clear speech, a speaking style used to mitigate communicative circumstances affecting the transmission or decoding of speech signal, often involves the enhancement of language-specific phonological contrasts, including laryngeal contrasts (e.g., Picheny et al., 1986). This study investigates the role of language dominance in the implementation of language-specific laryngeal contrasts in L2 clear speech. Two groups of Korean-English speakers (L1 Korean) were tested: a relatively less Korean-dominant L2-immersed group of sequential bilinguals (N = 30) and a strongly Korean-dominant L1-immersed group (N = 30), with dominance assessed based on the results of the Bilingual Language Profile (Birdsong et al., 2012). Participants read a set of English minimal pairs differing in the voicing of word-initial stops (e.g., tab vs. dab), and their acoustic enhancement strategies were compared with those of native English speakers (N = 20). As correlates of the English laryngeal contrast, voice onset time (VOT) and onset f0 were measured. Results showed that both bilingual groups enhanced English laryngeal contrast in clear speech via voiceless VOT lengthening, similarly to native English speakers, but to a smaller extent than native speakers. Both bilingual groups also implemented a greater degree of onset f0 difference between voiced and voiced English stops than native English speakers did, although no enhancement of this parameter was observed in their clear speech. Surprisingly, no significant differences were found between L2-and L1-immersed speakers, suggesting a lack of language immersion effect on the acoustic enhancement strategies in L2 clear speech. We discuss possible explanations for this finding and propose directions for future research.